Effectiveness of digital marketing in the mobile phone industry of Bangladesh - Shovon, Muntasir Mamun (BRAC Univeristy, 2017)
This internship report is submitted in a partial fulfilment of the requirements for the degree of Bachelor of Business Administration, 2017.